2020
DOI: 10.1111/vsu.13561
|View full text |Cite
|
Sign up to set email alerts
|

Use of a surgical safety checklist after implementation in an academic veterinary hospital

Abstract: Objective: To determine the use and barriers to uptake of a surgical safety checklist (SSC) after implementation in a veterinary teaching hospital. Study design: Voluntary online survey and retrospective study. Sample population: All personnel actively involved in the Ontario Veterinary College Health Sciences Centre small animal surgery service between October 2, 2018 and June 28, 2019. Methods: Surgical case logs and electronically initiated SSC were reviewed to calculate checklist use. The sample population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…Similar observations were noted by Menoud et al 25 . One study, based at a veterinary teaching hospital in Ontario, identified that ‘forgetting to use’ was the most frequently stated cause for SSC usage failure 26 . These veterinary studies are all small scale and single site based, with human behaviour likely influenced by individual workplace culture.…”
Section: Introductionsupporting
confidence: 63%
“…Similar observations were noted by Menoud et al 25 . One study, based at a veterinary teaching hospital in Ontario, identified that ‘forgetting to use’ was the most frequently stated cause for SSC usage failure 26 . These veterinary studies are all small scale and single site based, with human behaviour likely influenced by individual workplace culture.…”
Section: Introductionsupporting
confidence: 63%
“…In 1 study, despite the fact that 76% of survey respondents saw an immediate benefit to using an SSC, a complete checklist was used in only 47.7% of surgeries. 28 In a second study, 95% of survey respondents believed a complete SSC was used in every procedure-in reality, however, only 8.4% of these SSCs were completed in full. 29 These gaps demonstrate that opportunity exists to more widely and completely implement SSCs and further mitigate surgical and anesthetic risk in our patients.…”
Section: Reducing Surgical Complicationsmentioning
confidence: 94%
“…Two veterinary studies demonstrated that routine use of SSC in clinical practice is unfortunately the exception, not the norm. In 1 study, despite the fact that 76% of survey respondents saw an immediate benefit to using an SSC, a complete checklist was used in only 47.7% of surgeries 28 . In a second study, 95% of survey respondents believed a complete SSC was used in every procedure—in reality, however, only 8.4% of these SSCs were completed in full 29 .…”
Section: The Work Has Already Begunmentioning
confidence: 97%
See 2 more Smart Citations